Proyecto de factibilidad para la producción y comercialización de torta de camote en la ciudad de Loja. - Hurtado Duclós, Carla Estefanía (2012)
In the city and province of Loja sweet potato production is limited, and one of the key reasons for this phenomenon is the lack of awareness and appreciation of native production, lack of dietary protein, and it also possesses the Loja no businesses or entrepreneurs engaged in the processing of this raw material into finished products, not given an added value, in order to be placed on the market in different forms. One way of transforming the sweet potato is the preparation of cakes, however, in the Town of Loja not produced or marketed in any mall. In some cases, this production is performed only for family consumption because it is not considered as a means of production that can generate income and improve their quality of life. With the production of sweet potato cakes will contribute to improving health by eating a healthy, natural and nutritious food made from sweet potato in this project was also considered that by its execution will bring the productive development of areas rural areas where the potato is grown, improved quality of life for both the investor and indirect actors involved in it. The objective of this research was to determine the feasibility of the project for the production and marketing of sweet potato pie in the city of Loja, for it was necessary market research to determine the supply and demand for sweet potato pie in the Loja, perform technical study to determine the plant size, location and engineering required for the project of production and marketing of sweet potato cake, perform administrative and organizational study which determined the number of workers and management that requires company, make the financial study where the amount of investment, funding source, production costs and revenues that are generated in the project of sweet potato pie in the city of Loja, and finally realize the financial evaluation through indicators such as Net Present Value, Internal Rate of Return, Benefit Cost Ratio and so on., which allowed them to determine the feasibility of the project. Once you know the results of the objectives the decision was made to establish the company "Unique Cakes CAESH" EURL, law, duly registered in the Commercial Register of Canton Loja. The sole proprietorship limited liability is the legal organization formed by a natural person to engage in an exclusive economic activity, whose mission is to produce and cakes prepared from sweet potato pulp in the city of Loja, maintaining a high nutritional value, excellent customer service and competitive prices. The company vision is to become a solid and sustainable in the market, producing and marketing of sweet potato cakes of excellent quality. The methodology used to obtain all required information and meet the objectives, was the application of surveys to a sample of households in the city of Loja, with reference data from the latest census population projected to the year of project implementation (2012), thus achieving information that allowed us to determine the degree of acceptance of the sweet potato cake on the market, is unmet demand in the market Lojano. For the execution and implementation of project requires an investment of $ 37.648,36USD, the same will be recovered in 1years, 4 month, 2 days in the first year of project implementation results in a net profit of 28.052,79USD., The financing of this investment be covered by the project proponent. The financial evaluation allowed us to determine that the project is viable because the VAN is greater than one, and the Internal Rate of Return is 89,51% That is greater than the cost of capital.